Implementation of mobile commerce among university students in Malaysia - Kurnianingsih, Astuti (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2017)
The growth and development of technologies particularly wireless technology and mobile communication technology, have led to a rapid development of e-commerce. This new type of e-commerce of conducting transactions via mobile devices is known as mobile commerce. Although mobile commerce has been implemented in many developed countries, it still remain as an untapped area in some developing countries such as Malaysia. There is so much to explore and investigate from Malaysian context particularly amongst universities' students. The growth in the number of mobile devices has exceeded the number of mobile lines and other forms of communication. M-commerce has therefore continued to change the face of businesses by introducing new, faster, efficient and personalized benefits. With characteristics such as personalization, flexibility and wide spread usage, mobile commerce promises businesses in terms of new potential market and profitability. The aim of this research is to study the factors influencing students from universities in Malaysia to use mobile commerce through internet such as online shopping. Several factors such as perceived trust, perceived ease of use, security, perceived usefulness and perceived cost were analysed to find the most factors can influence the students to use Mobile Commerce. Respondents who were selected are studying in universities around Selangor, Malaysia such as IIUM, UKM and UiTM. Technology Acceptance Model (TAM) with the changes is the model that researcher proposed to find the factors that influence students in having the intention to use mobile commerce to shop online through the internet.